(untitled) (Research, Society and Development, 2020)
The article aimed to identify the effects of homophobia on the working environment of gay workers in financial institutions in the city of Maringá/PR. To achieve these objectives, ten homoaffective employees were interviewed individually. The results indicated that employees, for the most part, consider their organizations to be inclusive and concerned with sexual diversity. The occurrence of heteronormativity/heterosexism was verified, and all interviewees reported having suffered from homophobia in their work environment, either directly or indirectly. In addition, it was found that the employees, in general, consider themselves satisfied with their work and agree that their satisfaction is related to their sexual orientation. It is concluded that homoaffective sexual orientation has an impact on the satisfaction of gay employees in the investigated financial institutions and that, despite cases of homophobia, these institutions have shown concern about the inclusion of sexual diversity.